Role of echocardiography in diagnosis and management of complete papillary muscle rupture caused by myocardial infarction - Josip Vincelj; Stanko Biočić; Mario Udovičić; Mario Sičaja; Sandra Jakšić Jurinjak (Medicinski Glasnik, 2015)
Aim To evaluate the usefulness of echocardiography in the diagnosis of complete rupture of papillary muscle.